UFIDA (A) - Chen, E.; McFarlan, F. Warren (Franklin Warren); Yang, Bin ([London] : SAGE, 2016)
UFIDA was established in 1988. It developed quickly as Chinese enterprises started switching to computerized accounting methods, and businesses the world over started using information technology-based management tools. By 1991, UFIDA had become the largest financial management software provider in China, and has retained that top spot until the present. In 1996, UFIDA expanded into enterprise management software/ERP. In 2001 the company went public, listing on the Shanghai Stock Exchange. By 2002 UFIDA had taken a greater ERP market share in China than SAP, the international ERP provider, and UFIDA grew to become the largest Asia-headquartered enterprise management software provider.
Originally Published in: Chen, E., McFarlan, F.W., Yang, B. (2011). UFIDA (A). 0-310-111. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; UFIDA (Firm); Managerial economics -- Case studies; Competition -- Case studies; Computer software industry -- Management -- Case studies